The Influence Of Digital Marketing Strategy and Product Quality On Sales Of Culinary Micro, Small, And Medium Enterprises (MSMEs) In Kualuh Leidong District - Tumorang, Citra Agustina Br; Siagian, Nalom; Sinaga, Kepler (CV Putra Publisher, 2026)
The purpose of this study is to determine the effect of digital marketing strategies and product quality on the sales of micro, small, and medium enterprises in Kualuh Leidong District. The population in this study were culinary MSMEs in Kualuh Leidong District. The sampling technique used the Slovin formula, which is a sampling technique with special considerations so that it is worthy of being a Slovin sample and obtained a research sample of 60 respondents. The research variables used two variables, namely dependent and independent variables. For the independent variable (X) includes: digital marketing strategy (X1) and product quality (X2) and the dependent variable (Y) product sales. The data collection technique used was a questionnaire and multiple linear analysis with the equation obtained in this study is the analysis of Y = 8.263 + 0.228X1 + 0.154X2 it can be concluded that the constant value of 8.263 is the consistency value of the culinary MSME product sales variable in Kualuh Leidong District of 8.263. Based on the results of the partial hypothesis test (t test) shows that the digital marketing strategy (X1) has a positive and significant effect on product sales (Y) with a calculated t value of 3.280 and a significance value of 0.002 <0.05. Product quality (X2) also has a positive and significant effect on product sales (Y) with a calculated t value of 2.306 and a significance value of 0.025 <0.05. The results of the simultaneous test (F test) show that the digital marketing strategy and product quality together have a significant effect on the sales of culinary MSME products in Kualuh Leidong District, with a calculated F value of 7.253 and a significance value of 0.002 <0.05. And the results of the coefficient of determination test (R Square) show a value of 0.175, which means that the digital marketing strategy and product quality are able to explain variations in product sales by 17.5%, while the remaining 82.5% is influenced by other variables outside this study. Thus, it can be concluded that digital marketing strategies and product quality significantly influence the sales of culinary MSMEs in Kualuh Leidong District. Culinary MSMEs are advised to continuously optimize their digital marketing strategies and improve product quality to boost sales and business competitiveness